(untitled) (Journal of Population and Development, 2022)
Health is the primary responsibility of the government of every nation. A country with healthy citizens achieves success in the socio-economic development of the nation. The development of the nation does not mean the development of one class but the development of all classes. This study, tries to describe the socio-demographic and health status of women in Nepal. This study is completely based on secondary data sources and the data has been taken from various reports. The sex ratio of Nepal according to preliminary reports of census 2021 is 96. Currently literacy rate of women is 57 percent. Still, the practice of early marriage of women is culturally rooted in Nepal. Women get married earlier than men. Around 16 percent of women have children before the age of 20 years. Similarly, 17 percent of women are underweight and 22 percent are overweight. This indicates the problem of malnutrition is a serious problem in Nepal. Iron deficiency or anemia is a serious health problem for women in Nepal. The Nepal demographic and health survey 2016 has shown that 41 percent of women aged 15-49 years are anemic. Approximately 6 percent of pregnant women do not receive antenatal care, and 41 percent give birth at home, which can be dangerous for both the mother and the child. Women’s participation is essential for overall development. The government should pay attention to the development of the country by improving the overall health condition of women and coordinating every aspect of development.